1995
DOI: 10.2175/106143095x133103
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium adsorption of chlorophenols on granular activated carbon

Abstract: The adsorption of chlorinated phenols from aqueous solution on granular activated carbon was studied in batch reactors. Singlecomponent equilibrium adsorption data for the eight compounds in two concentration ranges at pH 7.0 and 30°C were fit well by both the Langmuir and the Freundlich equations. The adsorptive capacities at pH 7.0 increase from pentachlorophenol to trichlorophenols and are fairly constant from trichlorophenols to monochlorophenols. Equilibrium measurements were also conducted for 2,4,5-tric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…So far, PCP adsorption has been studied mainly with adsorbents such as powdered activated carbon (Lin et Biomass Preparation al., 1991;Siahpush et al, 1992), granular activated carbon (Nelson and Yang, 1995), and polyurethane foam Mycobacterium chlorophenolicum PCP-1 (DSM 43826) (Hu et al, 1994). The main purposes of these studies (Hä ggblom et al, 1994), was grown on a modified minwere to investigate the use of adsorbents and coimmobieral salt medium (Wittmann et al, 1994) del and Pfennig (1977), and 20 g/L glucose as the sole (1989) studied the adsorption and desorption (termed carbon and energy source.…”
Section: Methodsmentioning
confidence: 99%
“…So far, PCP adsorption has been studied mainly with adsorbents such as powdered activated carbon (Lin et Biomass Preparation al., 1991;Siahpush et al, 1992), granular activated carbon (Nelson and Yang, 1995), and polyurethane foam Mycobacterium chlorophenolicum PCP-1 (DSM 43826) (Hu et al, 1994). The main purposes of these studies (Hä ggblom et al, 1994), was grown on a modified minwere to investigate the use of adsorbents and coimmobieral salt medium (Wittmann et al, 1994) del and Pfennig (1977), and 20 g/L glucose as the sole (1989) studied the adsorption and desorption (termed carbon and energy source.…”
Section: Methodsmentioning
confidence: 99%
“…Many studies were conducted to test the adsorption of chlorophenols on surfaces such as GAC [10,24,25], montmorillonite [6], alumina pillared clays [3], and surfactant modified clays [6,24,26] in the last 20 years. Different adsorption isotherms were used to fit the adsorption data to account for the adsorption mechanism.…”
Section: Effect Of Ph On Adsorption Isothermsmentioning
confidence: 99%
“…In an equilibrium adsorption study, it was found that protonated species of PCP followed a linear adsorption isotherm, indicating a partitioning mechanism on hexadecyltrimethylammonium (HDTMA)-clays, whereas deprotonated species followed a Langmuir adsorption isotherm [6]. In contrast, adsorption of 2,4-DCP, 2,4,5-TCP, and 2,3,4,6-TeCP and PCP adsorption on GAC followed Langmuir isotherm [25]. A lower adsorption capacity of TeCP and PCP by GAC was found compared with DCP and TCP.…”
Section: Effect Of Ph On Adsorption Isothermsmentioning
confidence: 99%
See 1 more Smart Citation
“…For adsorbate and solvent the adsorption phenomenon depends on the differences between their chemical properties, structure and interactions (mutual and with solid surface). The adsorption of various series of different organic adsorbates was analyzed to find some correlations between the sorption experimental data and the properties of adsorbate and adsorbent [4,[10][11][12][13][14][15][16][17][18][19]. Many of benzene derivatives possess acidic or basic functional groups.…”
Section: Introductionmentioning
confidence: 99%